Surveillance and control of African Swine Fever in free‐ranging pigs in Sardinia. Issue 3 (25th February 2019) - Laddomada, Alberto; Rolesu, Sandro; Loi, Federica; Cappai, Stefano; Oggiano, Annalisa; Madrau, Maria Paola; Sanna, Maria Luisa; Pilo, Giovannantonio; Bandino, Ennio; Brundu, Diego; Cherchi, Simonetta; Masala, Sergio; et al.
SUMMARY: African swine fever (ASF) is a notifiable infectious disease, caused by the ASF virus (ASFV), which is a DNA virus belonging to the family Asfarviridae, genus Asfivirus . This disease has gained importance in the last decade after its spread in several countries in Eastern and Central Europe, and more recently, in China. Despite the efforts made to eradicate it, ASF is still present on the Mediterranean island of Sardinia (Italy) and has been since 1978. ASF risk factors on the island have been analysed in previous studies; the role of free‐ranging pigs in virus persistence has been suggested, but has not been fully elucidated. The most recent eradication plan provides more stringent measures to combat free‐ranging pigs and any kind of illegality in the pig sector. From December 2017 to June 2018, a total of 29 depopulation actions were performed in 13 municipalities in central Sardinia, during which 2, 281 free‐ranging pigs were culled and more than 50% of them were tested for ASFV and antibody presence (1, 218 and 1, 416, respectively). A total of 651 pigs were seropositive, with a mean seroprevalence of 53.4% (CI 95% = 50.6–56.3), and 38 were ASFV positive (virus prevalence = 2.6%; CI 95% = 2.1–3.0). To the best of our knowledge, the present study is the first to provide a complete evaluation of this millennial system of pig farming and ASFV prevalence in free‐ranging pigs. Furthermore, it has emphasised the necessity of combining the maintenance of an epidemiological surveillance program with continuous education of farmers and other people involved in pig husbandry, based on cultural and economic aspects.